Textile rectenna for RF energy harvesting - Silva, Fábio (2021)
Wearable devices are part of many people’s lives, however the batteries they need are a major limitation. In order to solve this problem, an energy harvesting system was studied and implemented, to replace the battery usage and thus enhance the device portability. It is composed by two antennas, one for transmitting and the other for receiving, and a rectifier circuit. The system was completely developed in textile, allowing the integration into the user’s clothing.